Cytochrome b-559 and proton conductance in oxygenic photosynthesis - Arnon, Daniel I. (1988)
Although cytochrome b-559 has long been known as a membrane-bound redox component closely linked to the reaction center of the oxygen-generating photosystem (PSII), its role in photosynthesis has remained obscure. This paper reports evidence and outlines a hypothesis in support of a “b-559 cycle”—i.e., a light-induced, cytochrome b-559-dependent, cyclic electron transport pathway around PSII that promotes translocation of protons from plastoquinol into the aqueous domain (lumen) of photosynthetic membranes (thylakoids). Light-induced proton transport coupled to light-induced electron transport is an essential aspect of energy transduction in photosynthesis because it generates an electrochemical proton gradient that drives ATP synthesis by the process of photosynthetic phosphorylation. The principal carrier of electrons and protons in thylakoids is the plastoquinone/plastoquinol couple. We propose that the b-559 cycle functions as a redox-linked proton pump that may operate jointly with the Rieske iron-sulfur pathway in oxidizing plastoquinol. The overall effect of such concerted oxidation of plastoquinol would be the translocation into the thylakoid lumen of two protons for each electron transferred from water to plastocyanin via plastoquinone.